2023
DOI: 10.3390/plants12030595
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tree Spacing on Yields of Alley Cropping Systems—A Case Study from Hungary

Abstract: Alley cropping is a specific agroforestry system, which is regarded as sustainable land use management, that could play a crucial role in climate change adaptation and mitigation. Despite its appealing attributes, farmers’ up-take of the system is slow in temperate regions. This study aims to contribute to scaling-up agroforestry through a case study in Hungary and to help to design productive alley cropping systems. We investigated which tree planting pattern of black locust (Robinia pseudoacacia L.) results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The reduction was 10-60% for the kharif season and 7.2-29.5% for rabi crops from the 2nd year to 8 years after planting, respectively. Similarly, Honfy et al, 2023 investigated the tree planting pattern of black locust (Robinia pseudoacacia L.) when intercropped with triticale (x Triticosecale W.) and observed that more the trees planted on a hectare, the higher the volume of the stand, and the less yield of triticale. Studies carried out by various researchers observed that a significant yield reduction of more than 70% was observed near the tree base (0-3 m) and about a 10-35% reduction up to 9 m away from the tree (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction was 10-60% for the kharif season and 7.2-29.5% for rabi crops from the 2nd year to 8 years after planting, respectively. Similarly, Honfy et al, 2023 investigated the tree planting pattern of black locust (Robinia pseudoacacia L.) when intercropped with triticale (x Triticosecale W.) and observed that more the trees planted on a hectare, the higher the volume of the stand, and the less yield of triticale. Studies carried out by various researchers observed that a significant yield reduction of more than 70% was observed near the tree base (0-3 m) and about a 10-35% reduction up to 9 m away from the tree (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A LER ≥ 1 epitomizes a positive or at least indifferent effect of ACS on-site productivity. For temperate conditions, LERs of between 0.94 and 1.35 have been determined for ACS with various planting patterns of black locust and triticale (x Triticosecale Wittmack) in Hungary [17]; of 1.41 for ACS with willow and spring wheat, potato (Solanum tuberosum L.) and squash (Cucurbita spec. L.) in the UK [18]; and of 0.98 for ACS with black locust, poplar and alfalfa (Medicago sativa L.) in a post-mining landscape in Brandenburg [19].…”
Section: Of 26mentioning
confidence: 99%
“…According to the knowledge of the authors, in Hungary, no countrywide estimate on the carbon sequestration of agroforestry systems has been made available yet. Honfy et al [29] carried out a case study of alley cropping systems of black locust (Robinia pseudoacacia L.) intercropped with triticale (× Triticosecale W.) and evaluated the land equivalent ratios (LER). They found that most of the tested treatments had favorable LER ratios when the trees were five years old [29].…”
Section: Introductionmentioning
confidence: 99%
“…Honfy et al [29] carried out a case study of alley cropping systems of black locust (Robinia pseudoacacia L.) intercropped with triticale (× Triticosecale W.) and evaluated the land equivalent ratios (LER). They found that most of the tested treatments had favorable LER ratios when the trees were five years old [29]. As LER ratios higher than one signify increased biomass production when compared to sole cropping, we can assume that the carbon sequestration of agroforestry systems is also higher than that of land used only for agricul-tural crop production.…”
Section: Introductionmentioning
confidence: 99%